Integral operators with rough kernels in variable Lebesgue spaces - Urciuolo, Marta (2020)
We study integral operators with kernels K(x, y) = k1(x- A1y) ⋯ km(x- Amy) , ki(x)=Ωi(x)|x|n/qi where Ω i: Rn→ R are homogeneous functions of degree zero,satisfying a size and a Dini condition, Ai are certain invertible matrices, andnq1+⋯+nqm=n-α,0≤α